Pathophysiology of Sore Throat Symptoms: A Comprehensive Review (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Sore throat, or pharyngitis, is a highly prevalent clinical symptom characterized by inflammation, pain, and irritation of the pharyngeal mucosa. It is a manifestation of various underlying conditions, most commonly viral and bacterial infections. This review delves into the pathophysiological processes underlying sore throat symptoms, including inflammatory cascades, neurogenic pain pathways, and immune-mediated tissue damage. We also explore the implications of these mechanisms for clinical practice, providing evidence-based recommendations for diagnosis and management. Specific case studies and illustrative tables are included to enhance understanding.